PENERAPAN KOMPRES SERAI HANGAT UNTUK MENGURANGI NYERI SENDI PADA LANSIA DI PACITAN - Devi Indah Anggraeni; Tri Susilowati (Jurnal Keperawatan Duta Medika, 2022)
Introduction: The number of elderly people who experience joint pain in the Tanjungsari Pacitan Health Center work area in 2019 totaled 313 patients, 2020 totaled 620 patients, 2021 totaled 337 patients, from this data the elderly who experience joint pain are female and male. Joint pain disease usually attacks the joint area, and if not treated quickly it will interfere with daily activities and interfere with comfort. Objectives: Describe the results of implementing the application of warm lemongrass compresses to reduce joint pain in the elderly. Methods; The type of research used in this research is descriptive with a case study design. Results: The pain scale before being given the application of warm lemongrass compresses on the pain scale respondents showed a moderate pain scale. The pain scale after being given a warm lemongrass compress shows a mild pain scale. There are differences in the level of pain scale development in respondents with joint pain before and after the warm lemongrass compress intervention. Conclusions:; There are differences in development before and after being given warm lemongrass compresses in the elderly.